2004
DOI: 10.1111/j.1067-1927.2004.012112.x-1
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of connective tissue growth factor and type I collagen mRNA expression by connective tissue growth factor antisense oligonucleotide during experimental liver fibrosis

Abstract: Transforming growth factor (TGF)-beta 1 is a major mediator of liver fibrosis. Connective tissue growth factor (CTGF) mediates TGF-beta 1 pro-fibrogenic effects in vitro, but its in vivo role is unknown. Both TGF-beta 1 and CTGF are overexpressed in hepatic stellate cells during liver fibrosis. We have used antisense oligonucleotides to examine the role of CTGF in carbon tetrachloride-induced liver fibrosis in mice. Mice received carbon tetrachloride together with CTGF or TGF-beta 1 antisense oligonucleotides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 48 publications
(45 reference statements)
2
40
2
2
Order By: Relevance
“…One potential alternative mechanism may reside in transcriptional repression of CTGF. Knockdown of CTGF abolishes collagen deposition in various in vitro and in vivo models (11,29,30,33). We showed that TGF-␤-stimulated CTGF expression is completely abolished by incubation with forskolin.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…One potential alternative mechanism may reside in transcriptional repression of CTGF. Knockdown of CTGF abolishes collagen deposition in various in vitro and in vivo models (11,29,30,33). We showed that TGF-␤-stimulated CTGF expression is completely abolished by incubation with forskolin.…”
Section: Discussionmentioning
confidence: 73%
“…Forskolin acts as a repressor of TGF-␤-mediated COL1A1/2 expression, subsequently leading to decreased intracellular and secreted amounts of collagen type I. This modulatory effect might in part be mediated by CTGF, as CTGF inhibition is reported to suppress excessive collagen deposition in various in vitro and in vivo models (11,29,30,33).…”
Section: Activation Of Adenylate Cyclase Attenuates Tgf-␤-induced Colmentioning
confidence: 99%
“…CTGF is specifically induced by TGF-β1 and is considered to be the downstream response element and effective molecule of TGF-β1. It has been reported that CTGF is the key regulator of extracellular matrix production and plays an important role in hepatic and renal fibrosis, thus the TGF-β1-CTGF signal pathway might be an effective target for reversal of hepatic fibrosis [9,10] . Peroxisome proliferator-activated receptors (PPAR), including α, β/δ and γ are a family of ligand-activated nuclear transcriptional factors that are emerging as important determinants of cell growth and differentiation [11] .…”
Section: Introductionmentioning
confidence: 99%
“…In response to exogenous CTGF, HSCs demonstrate increased migration, proliferation, adhesion, and expression of type I collagen (6,41). Blockade of CTGF synthesis by antisense oligonucleotides of CTGF resulted in downexpression of type I collagen mRNA in an animal model with experimental liver fibrosis (52). Overproduction of CTGF in a variety of fibrotic disorders, including hepatic fibrosis, is presumably secondary to the activation and production of TGF-␤.…”
mentioning
confidence: 99%